Rome ou la solution à tous les problèmes européens : Georg Moenius et le concept de romanité durant l´entre-deux-guerres - Joris Lehnert (Amnis)
This article focuses on the ideas of the Bavarian priest Georg Moenius who saw the Roman Catholic Church as the necessary tool to spiritually restore the European civilization in times of the crisis of the interwar period. Pacifist and virulent opponent of all nationalism (and soon especially of the national-socialism), he took leave of his diocese and expressed his thoughts through travel books containing his impressions of Italy and of France. From 1929 until his exile provoked by Hitler’s accession to power, he was editor of the Allgemeine Rundschau, a catholic Bavarian weekly journal, and worked on the diffusion and explanation of the necessity of Gonzague de Reynold’s concept of Romanitas. Admirer of Maurras, he frequented the circles of the Action française and translated into German Henri Massis’ programmatic work The Defense of the West which he introduced with a long manifest describing a new Christian Empire guided by Rom, on the model of the medieval Holy Roman Empire, as the response to all European problems.